HSA-nanobinders crafted from bioresponsive prodrugs for combined cancer chemoimmunotherapy–an in vitro exploration - Tubertini, Matilde; Menilli, Luca; Milani, Celeste; Martini, Cecilia; Navacchia, Maria Luisa; Nugnes, Marta; Bartolini, Manuela; Naldi, Marina; Tedesco, Daniele; Martella, Elisa; Guerrini, Andrea; Ferroni, Claudia; et al. (Frontiers in Chemistry, 2024)
Introduction: Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer still lacking effective treatment options. Chemotherapy in combination with immunotherapy can restrict tumor progression and repolarize the tumor microenvironment towards an anti-tumor milieu, improving clinical outcome in TNBC patients. The chemotherapeutic drug paclitaxel has been shown to induce immunogenic cell death (ICD), whereas inhibitors of the indoleamine 2,3- dioxygenase 1 (IDO1) enzyme, whose expression is shared in immune regulatory and tumor cells, have been revealed to enhance the anti-tumor immune response. However, poor bioavailability and pharmacokinetics, off-target effects and hurdles in achieving therapeutic drug concentrations at the target tissue often limit the effectiveness of combination therapies. Methods: This work describes the development of novel biomimetic and carrier-free nanobinders (NBs) loaded with both paclitaxel and the IDO1 inhibitor NLG919 in the form of bioresponsive and biomimetic prodrugs. A fine tuning of the preparation conditions allowed to identify NB@5 as the most suitable nanoformulation in terms of reproducibility, stability and in vitro effectiveness. Results and discussion: Our data show that NB@5 effectively binds to HSA in cell-free experiments, demonstrating its protective role in the controlled release of drugs and suggesting the potential to exploit the protein as the endogenous vehicle for targeted delivery to the tumor site. Our study successfully proves that the drugs encapsulated within the NBs are preferentially released under the altered redox conditions commonly found in the tumor microenvironment, thereby inducing cell death, promoting ICD, and inhibiting IDO1.